SAT0468 Is Early Treatment with Biologics Associated with a Better Long-Term Outcome in Patients with Polyarticular Juvenile Idiopathic Arthritis (JIA)?. (23rd January 2014) - Klotsche, J.; Minden, K.; Niewerth, M.; Seipelt, E.; Hammer, M.; Zink, A.; Horneff, G.
Abstract : Background: Approximately one in three children with polyarthritis is currently being treated with a biologic agent in Germany. Biologics are not only increasingly used more frequently in JIA, but also earlier in the disease course. However, there is limited evidence whether early treatment with biologics improves the long-term outcome of JIA patients. Objectives: To study whether the duration of disease until start of biologic treatment influences the long-term outcome in JIA. Methods: We investigated the effect of early biologic treatment on outcomes in 483 young adults who were included in the BiKeR (Biologics in Pediatric Rheumatology) and JuMBO (Juvenile arthritis Methotrexate/Biologics long-term Observation) register. Clinical characteristics, treatments and patient-reported outcomes were prospectively recorded in these patients from start of therapy with biologics into adulthood. The duration from onset of JIA until start of a biologic therapy was categorized into three groups (duration ≤1 year = early therapy, >1 to <5 years= middle, ≥5 years = late). The following outcomes were assessed: i) inactive disease (no active joint, ESR ≤ 20 mm/h, physician-gobal on numerical rating scale [NRS]=0), ii) functional status (HAQ), iii) history of joint operations/replacements, iv) patient-reported outcomes (quality of life, pain, fatigue). Propensity score adjusted differences in outcomes were analyzed by multinomial logistic regression analyses between the three groups. The propensity score was estimated by the covariates JIA category, functional status, and disease activity at baseline, year of study inclusion, age at last available documentation, and length of follow-up. Results: At the last follow-up, the patients were 21.4 (mean) years old (mean disease duration 12 years). The mean duration of follow-up in BiKeR/JuMBO was 6.6 years. About 90% of the patients were still treated with biologics (64% etanercept, 22% adalinumab). Patients with early treatment with biologics had significantly better outcomes at the follow-up. In the group with early biologic therapy, 39% of the patients had an inactive disease (late: 14%, p<0.001), and 63% reported no functional limitations based on the HAQ (late: 45%, p=0.048). Moreover, patients of the early treatment group reported less pain on a NRS (2.1 versus 3.1, p=0.003) and higher SF-36 physical health scores (49 versus 45, p=0.02) than those with late treatment. The three groups did not differ significantly in the SF-36 mental health scores. However, the rate of joint operations was also lower in the early therapy group (4%) compared to the group with ≥5 years duration from disease onset to therapy start (28%, p=0.01). No patient in the early treatment group had received a joint replacement until last follow-up, in contrast to 7% in the group with late biologic treatment start. Conclusions: An early biologic therapy is associated with a better long-term outcome in patients with severe JIA. Disclosure of Interest: J. Klotsche: None Declared, K. Minden Grant/research support from: Pfizer, AbbVie, M. Niewerth: None Declared, E. Seipelt: None Declared, M. Hammer: None Declared, A. Zink: None Declared, G. Horneff Grant/research support from: Pfizer, AbbVie, Roche